The History of Ghosts in Early Modern Europe: Recent Research and Future Trajectories - Edwards, Kathryn A. (History compass, 2012)
Although some scholars in the 1970s and 1980s noted the frequent appearance of ghosts in early modern European society, only in the last fifteen years have ghosts received more systematic study and most synthetic works are products of the last five years. Beginning with a definition of "ghost" that considers the early modern context, this article examines ghostly apparitions in a wide variety of fields ranging from the history of crime, drama, and gender to the more expected realms of the history of death and demonology. It also describes how literary scholars have used the concept of the "spectral" or "ghostly" to deconstruct early modern genres and how folklorists have continued their traditional classifications of ghost stories and moved into interpretation of ghosts' generic and psychological roots. Following an analysis of the ghost’s role in modern understandings of demonology and witchcraft, this article concludes by arguing for the need to integrate manuscript, archival, and print material on ghosts and to attempt transnational and transconfessional analysis of European beliefs about apparitions.